Oxidative Status, Iron Plasma Levels in Venous Thrombosis Patients - Salvatore Santo Signorelli; Andrea Barbagallo; Gea Oliveri Conti; Maria Fiore; Antonio Cristaldi; Margherita Ferrante (MDPI AG, 2024)
Exaggerated clot induces venous thrombosis (VTE); oxidative stress (OxS) can to be postulated as additional risk factor. This study evaluates firstly OxS by measuring surrogate biomarkers (malondialdehyde-MDA, 4-hydroxinonenal-4-HNE, superoxide desmutase enzyme (SOD)), secondly the iron (Fe) plasma level and thirdly the hepcidin protein (Hep) level in patients with VTE. A case control study was performed enrolling twenty hospitalized patients and an equal number of healthy individuals. In VTE patients, the following results were found. The MDA was 8.38 ± 0.5 µM/L, the 4-HNE measured 2.75 ± 0.03 µM/L and the SOD was 0.025 ± 0.01 U/mL. The I was 73.10 ± 10 µg/dL and the He was 4.77 ± 0.52 ng/mL. In the control group, the MDA measured 5.5 ± 0.6 µM/L, the 4-HNE 2.24 ± 0.021 µM/L and the SOD 0.08 ± 0.12 U/mL. The Hep was 2.1 ± 0.55 ng/mL and the Fe was 88.2 ± 9.19 µg/dL. Differences were statistically significant. Results suggest that in VTE there is activated OxS, Fe deregulation and over-production of Hep. Fe deregulation induces OxS, leading both to inflammation in the clot activator and stimulation of the pro-thrombotic status. The study highlights OxS and Fe and their regulation as intriguing indicators for risk of VTE.